Perbedaan Konsep Diri Antara Siswa Aktif Dan Siswa Pasif Dalam Aktifitas Pendidikan Jasmani Olahraga, Dan Kesehatan Di SDN 1 Slempit Kedamean Gresik - Nugraha Murdiansyah, Bayu (CV. Multi Kreasi Media, 2024)
Education in a broad sense can cover the entire life process of each individual and their environment. Education is not only focused on receiving information about science but is also focused on forming the self-concept of the individuals involved. One form of education that involves physical activity is physical education, sports and health. Where the focus of research in education is not only limited to grades but how to shape an image of good physical and spiritual health as well as achievements in the field of sports. The general aim of this research is to find out the description of the differences in self-concept between active students and passive students in physical education, sports and health activities. The specific aim of this research is to determine the extent of the differences in self-concept between active and passive students in physical education, sports and health activities at SDN 1 Slempit, in order to form a better self-image for students in the future. This research is quantitative descriptive. The research method used is an ex post facto method where the researcher does not control the independent variable directly because the manifestation of the variable has already occurred, or because the variable basically cannot be manipulated. The data collection instrument in this research used a questionnaire. In this study, the population members were class V students at SDN 1 Slempit, Kedamean District, Gresik Regency, totaling 36 students. Based on the results of calculations carried out in collecting data from two different populations, namely active students and active students and passive students in physical education, sports and health activities, the results of the calculations show that p value = 0.0001 is smaller than pα = 0 .05. Thus, there are differences in self-concept between active students and passive students in physical education, sports and health activities. This shows that physical education, sports and health activities are able to form self-concept (self-image) in students.